2007
DOI: 10.1136/gut.2005.086637
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor-like activity of gliadin, an alimentary protein: implications for coeliac disease

Abstract: Background: Gliadins, a family of wheat proteins, are central to the pathogenesis of celiac disease (CD). In addition to 'immunogenic' effects, gliadin directly affects cultured cells and intestine preparations, and produces damage in vivo, via a separate 'toxic' peptide, such as A-gliadin p31-43 (P31-43). Aims: Understanding the molecular mechanisms underlying direct non T-cell mediated effects of gliadin peptides, and assessing their potential role in promoting CD.Method: Gliadin effects were tested on a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(201 citation statements)
references
References 35 publications
9
180
0
11
Order By: Relevance
“…It has recently been reported that gliadin, a glycoprotein present in wheat and several other cereals and identified as the environmental trigger responsible for the autoimmune damage of the small intestine typical of CD (15), fully reproduces the effects of EGF on the actin cytoskeleton (16), effects that are very similar to those previously reported for zonulin (7,10,16). Furthermore, structural analysis revealed that the pre-HP2 ␀-chain includes an EGF motif that contains 6 spatially conserved cysteine residues that form 3 intramolecular disulfide bonds (Fig.…”
Section: Recombinant Zonulin Activates Egfr and Causes Teer Changes Tsupporting
confidence: 64%
“…It has recently been reported that gliadin, a glycoprotein present in wheat and several other cereals and identified as the environmental trigger responsible for the autoimmune damage of the small intestine typical of CD (15), fully reproduces the effects of EGF on the actin cytoskeleton (16), effects that are very similar to those previously reported for zonulin (7,10,16). Furthermore, structural analysis revealed that the pre-HP2 ␀-chain includes an EGF motif that contains 6 spatially conserved cysteine residues that form 3 intramolecular disulfide bonds (Fig.…”
Section: Recombinant Zonulin Activates Egfr and Causes Teer Changes Tsupporting
confidence: 64%
“…This leads to prolonged epidermal growth factor receptor inactivation, overexpression of transpresented interleukin (IL) 15/IL15 receptor-α complex as well as increased reactive oxygen species generation, and TG2 activation (16,(30)(31)(32). Such a complex cascade of intracellular events following gliadin exposure likely derails intracellular control systems thus disrupting Ca 2+ homeostasis by still unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial cell lines, IEC6 (rat, passage 36-46) and CaCo-2 (human, passage [30][31][32][33][34][35][36][37][38][39][40], were grown on Lab-Tek I chamber slides and stained for CXCR3 as described above. To localize CXCR3 expression in intestinal tissues, 4-”m sections were prepared, and laser capture microdissection (mouse tissue) or immunohistochemistry (human tissue) were performed as previously described.…”
Section: Cxcr3 Expression In Intestinal Cell Lines and Tissuesmentioning
confidence: 99%